PENGARUH UKURAN PERUSAHAAN, RETURN ON ASSETS, FINANCIAL LEVERAGE, DAN NET PROFIT MARGIN TERHADAP PRAKTIK PERATAAN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA 2012-2014 - Ni Putu Yeni Astiti (STIMI Handayani Denpasar, 2017)
Income smoothing practices is a common phenomenon and is one of the earnings management that is defined as a reduction in income likely fluctuations from year to year by moving income from year to year high earnings to periods that are less favorable. This study aimed to examine the influence of NPM, ROA, firm size and financial leverage on the income smoothing on companies listed in the Indonesia Stock Exchange. This study uses Eckel index to classify companies that do or do not do income smoothing practices. The sample used in this study were 68 companies listed on the Stock Exchange within three years from 2012 to 2014 with the selection purposive sampling method. The statistical analysis used in this study with descriptive statistics and logistic regression results from Eckel index menunjukkanadanya income smoothing practices undertaken by companies listed on the Stock Exchange. In the multivariate analysis of the four independent variables, it turns out all the variables significantly influence income smoothing practices.